Fungal Pericarditis—A Systematic Review of 101 Cases - Predrag Jancic; Stefan Milutinovic; Marshall Ward; Milan Radovanovic; Nikola Jovanovic; Marina Antic; Nikola Nikolajevic; Marija Petrovic; Dorde Jevtic; Adam Adam; Igor Dumic (Microorganisms)
Fungal pericarditis is a rare disease but its incidence has risen in parallel with the global increase in invasive fungal infections. This systematic review analyzes data from previously reported cases of fungal pericarditis to provide an improved understanding of the etiology, clinical presentation, management, and outcomes of this rare disease. We reviewed Medline and Scopus databases from 1 January 1990 to 29 January 2024 for case reports that documented the isolation of a fungal pathogen from pericardial fluid or tissue. Of the 2330 articles screened, 101 cases met the inclusion criteria. Patients with fungal pericarditis and the involvement of at least one other organ—usually the lungs, brain, or kidney—had worse outcomes than patients with isolated pericardial disease. Immunosuppression was reported in 50% of cases and was associated with worse outcomes in adults. Patients who presented with chest pain, received adequate empiric antifungal therapy, and underwent pericardiocentesis and pericardiectomy had improved survival. The most common isolated pathogens were Candida spp., followed by Aspergillus spp. and Mucor spp., with the latter two linked to worse outcomes. Only 35% of patients received empiric antifungal medications before the causative pathogen was identified, and mortality was associated with a delay in appropriate therapy. Immunosuppression, disseminated disease, and presence of shock/multiorgan failure were additional risk factors associated with death. Fungal pericarditis carries a mortality rate of up to 50%, with nearly half of patients being immunocompromised. Clinicians frequently do not consider fungal pericarditis in the differential diagnoses, which leads to delays in treatment and poorer outcomes. Further prospective multicenter studies are urgently needed to better understand the epidemiology, improve diagnostic testing and management, and decrease unacceptably high mortality in patients with fungal pericarditis.